Assessment of Subendocardial Contractile Function in Aortic Stenosis: A Study Using Speckle Tracking Echocardiography. Issue 3 (24th January 2013) - van Dalen, Bas M.; Tzikas, Apostolos; Soliman, Osama I. I.; Heuvelman, Helena J.; Vletter, Wim B.; ten Cate, Folkert J.; Geleijnse, Marcel L.
<x xml:space="preserve">Abstract</x> Background: Angina and an electrocardiographic strain pattern are potential manifestations of subendocardial ischemia in aortic stenosis (AS). Left ventricular (LV) twist is known to increase proportionally to the severity of AS, which may be a result of loss of the inhibiting effect of the subendocardial fibers due to subendocardial dysfunction. It has also been shown that the ratio of LV twist to circumferential shortening of the endocardium (twist‐to‐shortening ratio [TSR]) is a reliable parameter of subendocardial dysfunction. The aim of this study was to investigate whether these markers are increased in AS patients with angina and/or electrocardiographic strain. Methods: The study comprised 60 AS patients with an aortic valve area <2.0 cm2 and LV ejection fraction >50%, and 30 healthy—for age and gender matched—control subjects. LV rotation parameters were determined by speckle tracking echocardiography. Results: Comparison of patients without angina and strain (n = 22), with either angina or strain (n = 28), and with both angina and strain (n = 8), showed highest peak systolic LV apical rotation, peak systolic LV twist, and TSR, in patients with more signs of subendocardial ischemia. In a multivariate linear regression model, only severity of AS and the presence of angina and/or strain could be identified as independent predictors of peak systolic LV twist and TSR. Conclusions: Peak systolic LV twist and TSR are increased in AS patients and related to the severity of AS and symptoms (angina) or electrocardiographic signs (strain) compatible with subendocardial ischemia.